2021
DOI: 10.1021/acs.iecr.1c03208
|View full text |Cite
|
Sign up to set email alerts
|

Villermaux–Dushman Test of Micromixing Characterization Revisited: Kinetic Effects of Acid Choice and Ionic Strength

Abstract: The well-known Villermaux−Dushman system is nowadays widely used for examining the micromixing efficiency either in batch or continuous intensified reactors. However, a bibliographic review shows that kinetic data are too scattered for a reliable determination of the micromixing times. The Dushman reaction kinetics is then reexamined with the use of sulfuric and perchloric acids. The results confirm the fifth-order rate law. More precisely, the I − , H + , and IO 3 − dependence orders on the rate law are, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
(147 reference statements)
0
13
0
Order By: Relevance
“…The effects of incomplete dissociation of sulfuric acid in micromixing experiments have been discussed by other authors, ,,, , and can be observed in Figure a,b. Using equivalent proton concentrations and assuming the acids to be fully dissociated, one would expect the same final product distribution.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…The effects of incomplete dissociation of sulfuric acid in micromixing experiments have been discussed by other authors, ,,, , and can be observed in Figure a,b. Using equivalent proton concentrations and assuming the acids to be fully dissociated, one would expect the same final product distribution.…”
Section: Resultsmentioning
confidence: 63%
“…This is very likely due to the incomplete dissociation of sulfuric acid and the sulfate ions acting as a weak base. Furthermore, the revised model from Guichardon and Ibaseta shows an increase on the reaction rate coefficient with increasing ionic strength, and overestimates the reaction rate coefficient as much as 2 orders of magnitude at higher values of ionic strength as discussed by Wenzel et al It is inferred that the revised model must include additional modeling of the dissociation equilibrium, presumably in the form presented by Baqueiro et al…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Originally, the reaction was carried out with sulfuric acid in a borate buffer . As it was recognized that sulfuric acid cannot be regarded as fully dissociated, perchloric acid was proposed as a proton donor. Moreover, the borate buffer was substituted with a phosphate buffer since boric acid is classified as toxic for reproduction by the European Union’s Classification, Labelling and Packaging (CLP) Regulation and the Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH). , However, in experiments with identical setups, lower triiodide absorbances were measured in a phosphate buffer than in a borate buffer. , Since phosphoric acid is a polyprotic acid, both HPO 4 2– and H 2 PO 4 – could take part in the acid–base reaction, resulting in lower triiodide concentrations. In recent micromixing time calculations using the incorporation model, it was unclear to which extent HPO 4 2– and H 2 PO 4 – take part in the neutralization reaction .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the best accordance between both reaction rate constants is obtained with the results of Marshall for ionic strengths up to 1 mol L −1 , although the extended Debye−Huckel relation still provided a good agreement. 10 Nevertheless, the dependency of the ionic strength of the second dissociation constant of sulfuric acid complicates the usage of sulfuric acid, which is why perchloric acid was suggested as a proton donor for the Villermaux−Dushman reaction. Comparable micromixing experiments with sulfuric acid as the proton donor led to smaller triiodide concentrations than with perchloric acid.…”
mentioning
confidence: 99%